Markers for blood-brain barrier integrity: how appropriate is Evans blue in the twenty-first century and what are the alternatives? - Saunders, Norman R.; Dziegielewska, Katarzyna M.; Møllgård, Kjeld; Habgood, Mark D. (Frontiers in Neuroscience, 2015)
In recent years there has been a resurgence of interest in brain barriers and various roles their intrinsic mechanisms may play in neurological disorders. Such studies require suitable models and markers to demonstrate integrity and functional changes at the interfaces between blood, brain and cerebrospinal fluid. Studies of brain barrier mechanisms and measurements of plasma volume using dyes have a long-standing history, dating back to the late 19th-Century. Their use continues in spite of their known serious limitations in in vivo applications. These were well known when first introduced, but seem to have been forgotten since. Understanding these limitations is important because Evans blue is still the most commonly used marker of brain barrier integrity and those using it seem oblivious to problems arising from its in vivo application. The introduction of HRP in the mid 20th-Century was an important advance because its reaction product can be visualized at the electron microscopical level. Advantages and disadvantages these markers will be discussed together with a critical evaluation of alternative approaches. There is no single marker suitable for all purposes. A combination of different sized, visualisable dextrans and radiolabelled molecules currently seems to be the most appropriate approach for qualitative and quantitative assessment of barrier integrity.